PERSEPSI SOSIAL TENTANG STUNTING DI KABUPATEN TANGERANG - Silva Liem; Hana Panggabean; Rustono Marta Farady (Puslitbang Upaya Kesehatan Masyarakat, 2019)
ABSTRACT Stunting is an indicator of chronic malnutrition in the first 1000 days of a child’s life. This threatens the quality of human resources of Indonesia. The local communities generally interpret stunting as “short” and use different terms such as ‘kerdil’, ‘cebol’, ‘kuntet’, and ‘kuntring’. Having short posture is frequently perceived as heredity rather than as malnutrition. Inadequate meanings derived from social perception process may lead mothers to ignore such behavior that will increase risks of stunting and undermine community participation in government-led programme to reduce stunting. This qualitative study aims to describe facts on how community preceived stunted children. Data were obtained through field observation and in-depth interviews with four mothers having under-five-aged children in Tangerang. Thematic analysis was used to analyse the collected data. This study revealed that stunting is not being associated with health or nutrition issues. In fact, participants perceive stunted children as smart children. Holding on to such perception may jeopardize optimal community participation in government’s efforts to reduce stunting prevalences. Design of appropriate activities may need to consider social perception held by local communities where the intervention will be implemented. Keywords: Stunting, social perception, childhood nutrition ABSTRAK Stunting adalah indikator kekurangan gizi kronis dalam periode 1000 hari pertama kehidupan seseorang. Hal ini mengancam kualitas sumber daya manusia Indonesia. Masyarakat setempat pada umumnya memaknai stunting sebatas “berbadan pendek” dengan menggunakan istilah yang berbeda, misalnya ‘kerdil’, ‘cebol’, ‘kuntet’, dan ‘‘kuntring’’ sebagai akibat dari faktor keturunan. Perspektif persepsi sosial penting dalam pemaknaan tersebut, karena berpotensi mengabaikan perilaku berisiko anak stunting oleh para ibu dan menghambat partisipasi masyarakat dalam program pemerintah menurunkan kejadian stunting. Penelitian kualitatif ini bertujuan untuk mengetahui bagaimana masyarakat memaknai balita berbadan pendek. Data diperoleh melalui observasi dan wawancara mendalam dengan empat orang ibu yang memiliki anak balita di kabupaten Tangerang. Data diolah dengan analisis tematik. Hasil penelitian menunjukkan balita pendek tidak dikaitkan dengan masalah kesehatan maupun gizi, bahkan responden memandang anak ‘‘kuntring’’ sebagai anak yang pintar. Persepsi demikian dapat berdampak pada keterlibatan masyarakat yang tidak optimal dalam upaya pemerintah mengurangi kejadian stunting. Perencanaan intervensi pencegahan yang tepat perlu mempertimbangkan persepsi sosial yang berlaku dalam masyarakat. Kata kunci: Stunting, persepsi sosial, gizi anak balita